Corruption and Solid Waste Management in Mbarara Municipality, Uganda. (29th June 2020) - Gumisiriza, Pius; Kugonza, Sylvester
Abstract : Mbarara Municipality in Western Uganda has for many years struggled to manage municipal solid waste. Leaders in this municipality have mainly attributed this persistent problem to poor financing, failure to enforce existing solid waste management laws and regulations, limited community participation, deprived attitude by the public towards waste collection, and tendency of municipal dwellers to litter. No in-depth academic study in Mbarara Municipality has ever been done to expose and illustrate how corruption directly happens and influence solid waste management. This study fills this knowledge gap by illustrating how corruption influences poor solid waste management in Mbarara Municipality. The study finds that municipal technical officials, garbage truck drivers, their turn boys, garbage sorters, factory owners, and private land grabbers all involved in different forms of corruption have directly and indirectly turned solid waste collection and disposal into a very costly problem to the municipal council and the general public. The article recommends that fighting corruption in all its forms without fear or favor, encouraging them to play their role particularly in sorting waste, adoption of smart technologies, and putting in place measures that attract private investors while protecting the public can help in the effective management of solid waste in Mbarara Municipality.